2017
DOI: 10.1038/s41598-017-08953-4
|View full text |Cite
|
Sign up to set email alerts
|

Mouse strain differences in SSRI sensitivity correlate with serotonin transporter binding and function

Abstract: Selective serotonin reuptake inhibitors (SSRIs) bind 5-HT transporters, leading to the accumulation of 5-HT and amelioration of depression. Although different mouse strains show varying sensitivity to SSRIs in mouse models of depression, the underlying mechanism of these strain differences remains unclear. Here, the SSRI citalopram dose-dependently reduced immobility time in both the FST and TST in DBA/2J mice but not C57BL/6J mice, whereas fluoxetine showed the opposite results. Paroxetine similarly reduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 28 publications
(54 reference statements)
2
26
0
Order By: Relevance
“…Although further experiments are warranted to decipher the precise mechanisms by which the depletion of Cx43 produces positive effects on hippocampal 5‐HT tone specifically in response to fluoxetine, we then sought to determine to what extent these neurochemical changes in the hippocampus influenced the behavioural responses. As previously reported in C57BL/6 mice, we showed that a high dose of fluoxetine (ie 18 mg/kg) induced antidepressant‐like effects in the tail suspension test whereas a lower dose (5 mg/kg) failed to do so. One of the most remarkable results reported herein is that such a response was potentiated in Cx43 KD mice.…”
Section: Discussionsupporting
confidence: 86%
“…Although further experiments are warranted to decipher the precise mechanisms by which the depletion of Cx43 produces positive effects on hippocampal 5‐HT tone specifically in response to fluoxetine, we then sought to determine to what extent these neurochemical changes in the hippocampus influenced the behavioural responses. As previously reported in C57BL/6 mice, we showed that a high dose of fluoxetine (ie 18 mg/kg) induced antidepressant‐like effects in the tail suspension test whereas a lower dose (5 mg/kg) failed to do so. One of the most remarkable results reported herein is that such a response was potentiated in Cx43 KD mice.…”
Section: Discussionsupporting
confidence: 86%
“…C57BL/6J is one of the most widely used mouse strains in preclinic pharmacology and toxicology studies [ 32 , 33 ]. The choice of the animal strain is of particular importance when performing drug investigations and previous studies have indeed reported as different strains respond more or less effectively to the same compound [ 34 , 35 ], depending on several variables like different pharmacodynamics and drug metabolism. For instance Jin ZL et al [ 34 ] found that some murine strains do not respond to citalopram to the same extent and in a dose-dependent way.…”
Section: Discussionmentioning
confidence: 99%
“…To isolate DA transporter (DAT)-mediated [ 3 H]-DA uptake, fluoxetine (200 nM) and desipramine (100 nM) were applied to block [ 3 H]-DA uptake via the serotonin transporter and norepinephrine transporter, respectively. Plate-loaded samples were incubated at 22 °C for 5 min (Jin et al, 2017). Nomifensine (500 μM) was used for blanks.…”
Section: [ 3 H]-dopamine Uptakementioning
confidence: 99%